Spread of Traditional Chinese Medicine to the West and the Development of Sinology: A Case Study Based on the Translation of Traditional Chinese Medicine Literature by German Doctor Gottlieb Olpp - Wei-Man Yuan (Chinese Medicine and Culture)
German doctor Gottlieb Olpp played an important role in Sino-German medical exchanges during the late Qing dynasty. During his stay in China for more than 9 years, he wrote a large number of texts related to local Chinese medical and hygienic conditions. In these works, he introduced traditional Chinese medicine (TCM) and its situation at that time but also translated TCM literature. His translations and his achievements facilitated the development of sinology in Germany. Not only was he responsible for the development of the method used by German sinologists in translating TCM literature, but also his work gave an impetus to the combination of academic goals and current considerations in sinology studies. In this way, the study of TCM is the internal force driving the development of sinology.